Analisis Perkembangan Kognitif Anak Usia Dasar dan Implikasinya dalam Kegiatan Belajar Mengajar - Bujuri, Dian Andesta (Literasi: Jurnal Ilmu Pendidikan, 2018)
The human as human being should experience the development every time, including on the basic age of child (7-13 years old). One of important aspects of  human development is cognitive aspect. Cognitive development is an comprehensive development relating with thinking ability, such as the ability of thingking, reasoning, expressing idea, imagination and creativity. According to Piaget’s theory, the cognitive development of basic age child consists of two phases: the first is concrete operational phase (7-11 years old) that is a phase where the child has been able to function his/her mind to think logical, rational and objective, but it is just limited on the object concrete.  The second is formal operational phase (11-12 more years old) that is a phase where the child has used his/her mind to think a matter which will be or ought to be happening (hyphotheses) and a abstract matter. In spite of the same phase, cognitive development of child has difference in every age level that it is very significant to be known especially in education scope in teaching and learning process. Referred to new version of Talksonomi Bloom Theory, the child who is 7 years old has been at C1, C2 and C3 level but it is still limited, age 8 years is C2 and C3 level; age 9 years is C3 level which is high level; age 10 years is C3, C4 and C5 level which is limited, age 11 years is C4, C5 and C5 level; and 12 years more is C6 level which is better. The significance of comprehension about the cognitive ability level of child becomes reference to choose material lesson, to determine strategy, model and learning method. The purpose is to able to create effective learning and to be able to comprehend the material maximally which it is hopefully compatible with the belonging of child’s cognitive ability. Keyword : Cognitive Development, Basic Age Child, Teaching and Learning